2010
DOI: 10.1098/rspb.2010.0742
|View full text |Cite
|
Sign up to set email alerts
|

Motion perception and visual signal design in Anolis lizards

Abstract: Anolis lizards communicate with displays consisting of motion of the head and body. Early portions of long-distance displays require movements that are effective at eliciting the attention of potential receivers. We studied signal-motion efficacy using a two-dimensional visual-motion detection (2DMD) model consisting of a grid of correlation-type elementary motion detectors. This 2DMD model has been shown to accurately predict Anolis lizard behavioural response. We tested different patterns of artificially gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…These signals are given spontaneously by males to advertise their presence as they patrol their territories, as well as being directed toward other individuals during courtship and the settlement of territorial disputes (38)(39)(40). Theoretical predictions, supported by empirical data, have shown that the physical properties of head-bob displays in A. sagrei, particularly the square wave-like temporal pattern generated by rapid changes in head position, are highly conspicuous to visually oriented receivers, even when those receivers are inattentive (41,42). The amplitude of these movements determines the maximum distance from which the sensory system of a conspecific is stimulated effectively by the signal-what is termed the "active space."…”
mentioning
confidence: 48%
“…These signals are given spontaneously by males to advertise their presence as they patrol their territories, as well as being directed toward other individuals during courtship and the settlement of territorial disputes (38)(39)(40). Theoretical predictions, supported by empirical data, have shown that the physical properties of head-bob displays in A. sagrei, particularly the square wave-like temporal pattern generated by rapid changes in head position, are highly conspicuous to visually oriented receivers, even when those receivers are inattentive (41,42). The amplitude of these movements determines the maximum distance from which the sensory system of a conspecific is stimulated effectively by the signal-what is termed the "active space."…”
mentioning
confidence: 48%
“…Most notably would be variation in terms of amplitude and movement direction. Angular speed differences between signal and noise have been the subject of recent attention (Peters and Evans, 2003;Ord et al, 2007Ord et al, , 2010Fleishman and Pallus, 2010;Pallus et al, 2010), while differences between signal and noise in terms of the direction of movement also might be a useful avenue of inquiry, although it has not received as much attention in the literature (but see Peters et al, 2008;How et al, 2009). Movement amplitude and direction information could be extracted from the raw data we have collected.…”
Section: Extending the Methodologymentioning
confidence: 99%
“…Furthermore, Peters and Evans (2003) employed the same methodology to compare velocity signatures from lizard signals and plant sequences in order to estimate the relative conspicuousness of each motor pattern in the lizard display. This led to a much better understanding of motion signal structure and opened the path to many studies on the influence of the environment on lizard signaling behavior (Leal and Fleishman, 2004;Ord et al, 2007Ord et al, , 2010Peters et al, 2007Peters et al, , 2008Ord and Stamps, 2008;Fleishman and Pallus, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations